Measures to strengthen the internal control system of the Mariano Marcos Memorial Hospital and Medical Center, Batac City, Ilocos Norte, Philippines - Almazan, Kristine Angelie G. (Laoag City, Ilocos Norte : [s.n.], 2018)
This study formulated measures to strengthen the internal control system of the Mariano Marcos Memorial Hospital & Medical Center (MMMH&MC. The descriptive research design was employed utilizing two sets of questionnaire designed in a checklist format and in a rating scale to gather data from the 456 employees and 101 clients of the MMMH & MC. The gathered data were analyzed and interpreted using frequency, percentage, and Pearson r of correlation.
Bibliography: pages 95-98.
CHED-La Union
Keywords: Hospital management